2012
DOI: 10.1016/j.aju.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Positions for percutaneous nephrolithotomy: Thirty-five years of evolution

Abstract: ObjectivesTo present the chronological development of the different positions described for percutaneous nephrolithotomy (PCNL), in an attempt to identify the reasons for their development and to highlight their specific advantages and disadvantages.MethodsPrevious reports were identified by a non-systematic search of Medline and Scopus.ResultsThe classic prone position for PCNL was first described in 1976. The technique was gradually standardised and PCNL with the patient prone became the generally accepted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 45 publications
0
49
1
Order By: Relevance
“…Complete supine PCNL would have a better kidney fluoroscopic view compared to semisupine position because the vertebra would not overlap the fluoroscopic view. [6,7] Stone composition has been used to anticipate the success rate of ESWL. However, it has been found that the stone construction is more important than its composition.…”
Section: Introductionmentioning
confidence: 99%
“…Complete supine PCNL would have a better kidney fluoroscopic view compared to semisupine position because the vertebra would not overlap the fluoroscopic view. [6,7] Stone composition has been used to anticipate the success rate of ESWL. However, it has been found that the stone construction is more important than its composition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with staghorn calculi and obese patients develop fewer complications at supine position (25). In addition, other studies indicated that urologists should select the type of position according to the patient's conditions (20,23). In this study, in TUL the patients' blood pressure was more stable at lateral position and therefore this position can be considered a suitable position for patients undergoing spinal anesthesia.…”
Section: Discussionmentioning
confidence: 64%
“…Lateral and supine positions are considered safe positions in kidney surgeries and therefore recommended for patients at high risk (15,22). The patients feel more comfortable in these positions that are generally convenient and low-risk positions (23). However, the findings of a review of supine and prone positions in percutaneous nephrolithotomy showed that controversies over the type of position remain with no difference between these two positions (24).…”
Section: Discussionmentioning
confidence: 99%
“…2 Currently, the European Association of Urology (EAU) clinical guidelines panel recommends percutaneous nephrolithotomy as the first-line treatment for kidney stones measuring 2 cm, lower pole stones of 1.5 cm, and staghorn stones. [3][4][5] It has almost completely replaced open surgery, because it is less invasive, safer, and more effective (stone-free rates of 78 to 95%). 6 Traditionally, the prone position was exclusively considered for renal access.…”
Section: Introductionmentioning
confidence: 99%